Remotely Piloted Aircraft Systems: A Human Systems Integration Perspective. (September 2014) - Cooke, Nancy J.; Bennett, Winston; Dougherty, John; Gawron, Valerie; Neville, Kelly; Rowe, Leah; Shattuck, Lawrence
For over a decade the human factors of Remotely Piloted Aircraft Systems (RPAS, but also known as Unmanned Aerial Systems-UAS or Unmanned Aerial Vehicles –UAV) has been the continued focus of a community of scientists and engineers. Their efforts have been highlighted in various workshops, conferences and books and range from the design of effective ground control stations to crew coordination, spatial disorientation, supervisory control of multiple vehicles, soda straw views of camera feed, and training and selection. Much progress has been made. But new problems are surfacing of a different, more complex nature. Current pressing issues such as the integration of UAS in the national airspace, training and certification of civilian pilots, or exploitation of sensor data from these platforms and concomitant privacy concerns fall within the scope of the discipline of Human Systems Integration (HSI). This panel will highlight several human systems integrations issues surrounding RPAS and will engage the audience in discussion of those issues.